EFFORTS TO IMPROVE THE STUDENTS’ LEARNING OUTCOMES IN MATHEMATICS BY USING TGT COOPERATIVE LEARNING MODEL OF SMAN 10 PEKANBARU - Yusniar (UIR PRESS, 2021)
Mathematics is a tool to develop ways of thinking. Mathematics is a science that provides a universal for human. Logical thinking framework in humans. Student motivation is also very low to learn mathematics. They feel bored because for them mathematics is a scourge and they only rely on clever friends without trying to be able to do it themselves. Team game tournament learning model using tournament games where student compete with other team members, will foster student motivation and entusiasm in learning model students are expected to improve learning outcomes. In this sudy the test result are said to have improved student learning outcomes, if there is an increase in the average class in each cycle, the aplication of the Team Games Tournament (TGT) learning outcomes in mathematics subject matter in mathematical logic where an increase the average value of the class that is that is at the time before the action 66,70 increased again in cycle I then increased again in cycle II 80,13 thus it can be conclude that the aplication of the learning models of Team Games Tournament (TGT) can improve the mathematics learning outcomes of class X students 2nd SMA Negeri 10 Pekanbaru.